Building A Traditional Medicine Inventory Application With The Concept Of Object Oriented Programming Using The Java Programming Language - Ispandi Ispandi; Rahdian Kusuma Atmaja; Adjat Sudradjat; Rino Ramadan (Journal of Information System, Informatics and Computing, 2022)
Until now the stock data of traditional medicines is still not computerized and requires an information system that supports and assists the data processing in this store. The distribution of traditional medicines still uses a manual work system, making it possible during the process there were errors in recording, inaccurate reports made and delays in finding the required data. The design of this information system is the best solution to solve the problems that exist in traditional medicine distributors, as well as with a computerized system an effective and efficient activity can be achieved in supporting activities at traditional medicine distributors so that the procurement system can be more conducive than the conventional medicine system.